2020
DOI: 10.1093/ajcp/aqaa186
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study on the Role of Estrogen, Progesterone, and Their Classical and Nonclassical Receptors in Cutaneous Neurofibromas of Individuals With Neurofibromatosis 1

Abstract: Objectives To evaluate the expression of progesterone receptor (PR), estrogen receptor (ER), and G protein–coupled estrogen receptor 1 (GPER-1) in cutaneous neurofibromas (cNFs) and their correlation with demographic, clinical, and laboratory data of individuals with neurofibromatosis 1 (NF1). The association of PROGINS polymorphism and PR expression in cNFs, as well as the serum steroidal hormones and the number of cNFs, was investigated. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…26 Gonadal hormones may lead to neurofibroma development, acting via a noncanonical pathway through GPER-1. 27 Case reports also demonstrate increased tumour growth in girls receiving depot progesterone preparations, but not in those receiving combined oral contraceptive pills. 27,28 Since the effects of progesterone are more established in girls and women with TS and NF1, use of progesterone should preferably be restricted to a maximum of ten days every month rather than a daily combined estrogen plus progesterone pill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Gonadal hormones may lead to neurofibroma development, acting via a noncanonical pathway through GPER-1. 27 Case reports also demonstrate increased tumour growth in girls receiving depot progesterone preparations, but not in those receiving combined oral contraceptive pills. 27,28 Since the effects of progesterone are more established in girls and women with TS and NF1, use of progesterone should preferably be restricted to a maximum of ten days every month rather than a daily combined estrogen plus progesterone pill.…”
Section: Discussionmentioning
confidence: 99%
“…27 Case reports also demonstrate increased tumour growth in girls receiving depot progesterone preparations, but not in those receiving combined oral contraceptive pills. 27,28 Since the effects of progesterone are more established in girls and women with TS and NF1, use of progesterone should preferably be restricted to a maximum of ten days every month rather than a daily combined estrogen plus progesterone pill. Close monitoring is warranted in these women for any increase in the number and size of neurofibroma, any new appearance or worsening of neurologic symptoms and worsening of visual acuity due to progression of optic glioma.…”
Section: Discussionmentioning
confidence: 99%
“…An increased progesterone receptor expression is associated with more cNFs and an increased proliferation index. 6 The absence of an association with male gender might indicate a lower impact of male hormonal changes on the growth of cNFs. We also found that a pubertal flare of cNFs was associated with the risk of having more than 100 neurofibromas.…”
mentioning
confidence: 99%